Anachronisme et humour : de l’usage intempestif de l’anachronisme dans la fiction en costumes - Bernard Papin (Mise au Point)
After defining anachronism as a rhetorical process, this article aims to highlight its humorous effects - particularly untimely in the diegetic universe where one a priori expects the least: historical fiction . It explores the types of humour anachronism results from, in between "burlesque mockery" and "satirical pastiche" (Gérard Genette). But anachronism does not make everyone laugh, it is also a form of humour that may ultimately be controversial and become a tool of "distinction" through the cultural complicity required from the reader or the viewer. Finally, one wonders if the sole purpose of anachronism is to amuse the spectator or if it contributes to other enhancement strategies of a target audience.